Modified Posterior Arm Flap for Axillary Hidradenitis Suppurativa. Issue 1 (January 2022) - Thomson, David R.; Saltrese, Songtum; Mehdi, Syed
Abstract : Introduction: Hidradenitis suppurativa (HS) is a chronic, inflammatory condition of the apocrine sweat glands present in 1% to 4% of the adult population, with twice greater prevalence in females. Surgical excision is the criterion-standard treatment for advanced, grade III disease, characterized by extensive and recurrent abscesses and interconnected sinus tracts. Numerous reconstructive methods have been used to cover the resulting defects, including secondary intention healing, use of skin grafts, and a wide range of locoregional flaps. Methods: The modified posterior arm flap has been developed for reconstruction of axillary defects after radical excision of HS. Based on perforating vessels from the axillary artery first identified by Masquelet, a brachioplasty-like incision is used to keep the donor site closure relatively hidden on the posteromedial aspect of the inner arm. Results: Eight modified posterior arm flaps have been undertaken in 6 patients, all women (mean age, 35 years; range, 22–51 years) from 2014 to 2019. All patients had complete resolution of their HS symptoms with no incidences of recurrence at mean follow-up of 15 months. All reported satisfaction with the aesthetic and functional outcomes of the procedure Discussion: We present a novel modification of the posterior arm flap for the treatment of advanced axillary HS with good functional and aesthetic outcomes and no incidences of recurrence.